Quantum Analog Annealing of Gain‐Dissipative Ising Machine Driven by Colored Gaussian Noise (Adv. Theory Simul. 3/2022). Issue 3 (10th March 2022) - Liao, Zhiqiang; Ma, Kaijie; Sarker, Md Shamim; Tang, Siyi; Yamahara, Hiroyasu; Seki, Munetoshi; Tabata, Hitoshi
Abstract : Quantum Analog Annealing of Gain‐Dissipative Ising Machine Driven by Colored Gaussian Noise In article number 2100497, Zhiqiang Liao, Hiroyasu Yamahara, and co‐workers utilize noise dispersion as a hyperparameter to modulate the performance of a gain‐dissipative Ising machine. The work proves the reddening noise can suppress random spin switching, so that the Ising machine can better find the ground state. The cover depicts the superior performance of red‐noise‐driven Ising machine in domain clustering dynamics.